Men in the middle local priests in early medieval Europe - Patzold, Steffen 1972-; Rhijn, Carine van (Ergänzungsbände zum Reallexikon der Germanischen Altertumskunde, 2016)
This volume studies local priests as central players in small communities of early medieval Europe. As clerics living among the laity, priests played a double role within their communities: that of local representatives of the Church and religious experts, and that of owners of land and other goods. By virtue of their membership of both the ecclesiastical and the secular world, they can be considered as ‘men in the middle’: people who brought politico-religious ideas and ideals to secular communities, and who linked the local to the supra-local via networks of landownerhsip. This book addresses both roles that local priests played by approaching them via their manuscripts, and via the charters that record transactions in which they were involved. Manuscripts once owned by local priests bear witness to their education and expertise, but also indicate how, for instance, ideals of the Carolingian reforms reached the lowest levels of early medieval society. The case-studies of collections of charters, on the other hand, show priests as active members of networks of the locally powerful in a variety of European regions. Notwithstanding many local variations, the contributions to this volume show that local priests as ‘men in the middle’ are a phenomenon shared by the early medieval world as a whole